Use, calibration and verification of agroecological models for boreal environments: A review. Issue 1 (29th April 2022) - Forster, Daniel; Helama, Samuli; Harrison, Matthew T.; Rotz, Clarence Alan; Chang, Jinfeng; Ciais, Phillippe; Pattey, Elizabeth; Virkajärvi, Perttu; Shurpali, Narasinha
Abstract: Past assessments report negative impacts of the climate crisis in boreal areas; but milder and shorter winters and elevated atmospheric CO2 may provide opportunities for agricultural productivity potentially playing a significant role in future food security. Arable cropping systems are expanding in boreal areas, but the regional mainstay will likely continue to be livestock production. Agroecological models can when appropriately calibrated and evaluated, facilitate improved productivity while minimising environmental impacts by identifying system interactions, and quantifying greenhouse gas emissions, soil carbon stocks and fertiliser use. While models designed for temperate and tropical zones abound, few are developed specifically for boreal zones, and there is uncertainty around the performance of existing models in boreal areas. We reviewed model performance across boreal environments and management systems. We identified a dearth of modelling studies in boreal regions, with the publication of three or less papers per year since the year 2000, constituting a significant research gap. Models IFSM and BASGRA_N performed best in grassland production, DNDC best in predicting soil N2 O and NH3 emissions. No model outperformed all others, strengthening the case for ensemble modelling. Existing agroecological models would be worthy of further evaluation, providing model improvements designed for boreal systems. Abstract : Climate change presents both risks, and potentially opportunities for boreal regions. BUT…agricultural planning needs well‐calibrated and validated models to help avoid irreversible mistakes.